2020
DOI: 10.1681/asn.2019101060
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-δ Mediates Kidney Tubular Injury in Cold Storage–Associated Kidney Transplantation

Abstract: BackgroundKidney injury associated with cold storage is a determinant of delayed graft function and the long-term outcome of transplanted kidneys, but the underlying mechanism remains elusive. We previously reported a role of protein kinase C-δ (PKCδ) in renal tubular injury during cisplatin nephrotoxicity and albumin-associated kidney injury, but whether PKCδ is involved in ischemic or transplantation-associated kidney injury is unknown.MethodsTo investigate PKCδ’s potential role in injury during cold storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 62 publications
(88 reference statements)
5
34
0
Order By: Relevance
“…Basic research (6,7) and clinical trial (8) revealed that inhibition of proximal tubular cell death with caspase inhibitors during cold storage improves graft function and histology. Moreover, we (9) and others (10)(11)(12)(13) identified intrinsic mitochondrial pathway of apoptosis in cold storage/transplantation kidney injury. Despite these findings, the cellular and molecular mechanism of cold storage/transplantation kidney injury remains elusive and there is an urgent need for effective renoprotective approaches.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Basic research (6,7) and clinical trial (8) revealed that inhibition of proximal tubular cell death with caspase inhibitors during cold storage improves graft function and histology. Moreover, we (9) and others (10)(11)(12)(13) identified intrinsic mitochondrial pathway of apoptosis in cold storage/transplantation kidney injury. Despite these findings, the cellular and molecular mechanism of cold storage/transplantation kidney injury remains elusive and there is an urgent need for effective renoprotective approaches.…”
Section: Introductionmentioning
confidence: 77%
“…The kidneys from donor mice were transplanted into syngeneic recipients following previously described procedures with minor modifications (9,21). The donor mice were anesthetized with pentobarbital (50 mg/kg intraperitoneally).…”
Section: Kidney Cold Storage/transplantationmentioning
confidence: 99%
See 3 more Smart Citations